Vitronectin and Substitution of a β-Strand 5A Lysine Residue Potentiate Activity-neutralization of PA Inhibitor-1 by Monoclonal Antibodies against α-Helix F - Schousboe, Susanne L.; Egelund, Rikke; Kirkegaard, Tove; Preissner, Klaus T.; Rodenburg, Kees W.; Andreasen, Peter A. (Thrombosis and Haemostasis, 2000)
Some monoclonal antibodies against plasminogen activator inhibitor-1 (PAI-1) are able to inhibit its reaction with its target proteinases. We have characterized the effect on PAI-1 of two monoclonal antibodies, Mab-2 and Mab-6, with overlapping epitopes in a sequence encompassing α-strand 1A, α-helix F, and the loop connecting α-helix F and β-strand 3A (the hF/s3A loop). Mab-2 reduced the inhibitory activity of wild type PAI-1 and almost totally abolished the inhibitory activity of a PAI-1 variant harboring an Ala substitution of Lys 325 (335 in the α1-proteinase inhibitor template residue numbering) in α-strand 5A. In both cases, the neutralizing effect of the antibody was strongly potentiated by vitronectin. Mab-6 had no effect on wild type PAI-1, but reduced the inhibitory activity of the K325A variant. The effect of Mab-6 was not potentiated by vitronectin. With both Mab-2 and Mab-6, the neutralization of PAI-1 activity was associated with PAI-1 substrate behaviour. Mab-2, but not Mab-6, prevented vitronectin from rescuing PAI-1 from cold-induced substrate behaviour. We propose that the antibodies act by weakening the anchoring of α-helix F to the adjacent structures, resulting in an increased flexibility of α-strand 5A and the hF/s3A loop and a changed conformational response to the binding of vitronectin in the α-helix E region. The potentiating effect of vitronectin on neutralization of PAI-1 by antibodies is a novel concept in the development of compounds for neutralizing PAI-1 in vivo.
Keywords: Serpins; serine proteinases; thrombosis; cancer